1974
DOI: 10.1037/h0035677
|View full text |Cite
|
Sign up to set email alerts
|

A ratio rule from integration theory applied to inference judgments.

Abstract: The 5s judged the likelihood that a sample had come from 1 of 2 binary urns of specified proportions of red and white beads. The compositions of the sample and of the 2 urns were varied in a 3-way design. A ratio model from integration theory fit the data quite well. The response is treated as a resultant of 2 competing response tendencies that reflect the felt likelihoods that the sample comes from either urn. A novel application of analysis of variance for nonlinear models was employed in the test of fit. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
32
0

Year Published

1975
1975
2006
2006

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(34 citation statements)
references
References 22 publications
2
32
0
Order By: Relevance
“…The probability of picking an urn, the relative proportion of beads in each urn, the sample size, and the sample makeup can be varied. The typical result is that subjects behave less optimally than predicted by Bayes's theorem (e.g., Leon & Anderson, 1974).…”
Section: Previous Rejections Of Optimal Behaviormentioning
confidence: 99%
See 1 more Smart Citation
“…The probability of picking an urn, the relative proportion of beads in each urn, the sample size, and the sample makeup can be varied. The typical result is that subjects behave less optimally than predicted by Bayes's theorem (e.g., Leon & Anderson, 1974).…”
Section: Previous Rejections Of Optimal Behaviormentioning
confidence: 99%
“…Consider a test of the Bayesian model in situations in which subjective base rates are assumed to be equal to objective base rates. In these cases, performance falls short of the predictions of Bayes's theorem (Leon & Anderson, 1974). Central to the current theoretical framework, however, is the evaluation stage that transforms the objective source of information into some subjective value.…”
Section: Previous Rejections Of Optimal Behaviormentioning
confidence: 99%
“…However, studies with artificial data are greatly needed to assess minimum design requirements that will allow real deviations from the model to be detected. These studies need to be done for models that are empirically reasonable, and inherently nonadditive, such as the averaging model with unequal weighting, and the ratio model developed in information integration theory (Anderson & Farkas, 1975;Leon & Anderson, 1974;Oden, 1974).5…”
Section: Error Theory For Nonmetric Analysismentioning
confidence: 99%
“…The methodological context in which the issues are evaluated. An important methodological point surfaced when Leon and Anderson (1974), using a within-subjects design, found that the judgments of participants in a two-urn task did not reflect base rate neglect; instead, judgments varied appropriately with changes in urn composition (corresponding to base rate) and sample size (corresponding to case cue accuracy). Similar findings have been reported by Ward (1975).…”
mentioning
confidence: 99%